Organic farming and sustainable agriculture in Malaysia: organic farmers' challenges towards adoption - Tiraieyari, Neda; Hamzah, Azimi; Abu Samah, Bahaman (Canadian Center of Science and Education, 2014)
Agriculture in Malaysia is characterised by high levels of fertiliser and manure applications and consequently environmental pollution. Sustainable agriculture and organic farming are being promoted by the government as a way of eliminating unsustainable agriculture. Despite the benefits that organic farming brings to farmers and environments, its adoption rate is still low among Malaysian farmers. A study of organic farmers in the Cameron Highlands was conducted to reveal the challenges that have been occurred with regard to adoption of the practice. The results indicate that organic farmers face challenges with regard to land tenure, certification processes, hiring foreign workers, marketing, training and extension services and governmental support. Issues and challenges were discussed. The paper concludes with some recommendations.